Scientific support for electrodiagnosis - Royal, F. Fuller; Royal, Daniel F. (British Homeopathic Journal, 1991)
The use of acupuncture, homœopathy and electrodermal instruments is increasing among physicians. Federal and state regulatory agencies have recently stepped up their investigations into the use of electrodiagnostic devices. A review of the history of medicine, the advent of electrodiagnosis and how it relates to acupuncture and homœopathy, past and present research, scientific support and future possibilities is presented. Scientific concepts of holism and nonlinear physics provide a new medical paradigm, quantum morphodynamics.